Kiribati : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper focuses on recent developments with Kiribati's Revenue Equalization Reserve Fund (RERF). The paper also examines fiscal aspects of climate change, and considers options for improving fishing license fees, which remain an important source of revenue. It also analyzes recent developments and the outlook for remittances to Kiribati, which is another important source of external revenue and brings important economic benefits, such as reducing poverty and stabilizing national income.